2013
DOI: 10.1210/jc.2012-3949
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Bone Marrow Fat Associated With Lower Trabecular BMD and Prevalent Vertebral Fracture in Older Adults

Abstract: Higher marrow fat correlated with lower trabecular, but not cortical, BMD in older women but not men. Higher marrow fat was associated with prevalent vertebral fracture in men, even after adjustment for BMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(183 citation statements)
references
References 29 publications
9
169
2
3
Order By: Relevance
“…The late perimenopause, in particular, is associated with rising FSH levels in the face of normal estrogen (4), raising the question whether estrogen deficiency is the sole cause of these physiologic aberrations. Third, bone marrow adiposity, often seen as a function of aging and sex steroid deficiency, is linked with osteoporosis (21,22). These associations lay the basis not only for overlapping molecular mechanisms that underpin both osteoporosis and obesity, but also for a new therapeutic approach to treat these two diseases simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The late perimenopause, in particular, is associated with rising FSH levels in the face of normal estrogen (4), raising the question whether estrogen deficiency is the sole cause of these physiologic aberrations. Third, bone marrow adiposity, often seen as a function of aging and sex steroid deficiency, is linked with osteoporosis (21,22). These associations lay the basis not only for overlapping molecular mechanisms that underpin both osteoporosis and obesity, but also for a new therapeutic approach to treat these two diseases simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetically preprogrammed pathway for marrow-derived MSCs appears to be osteogenic; however, the potential for adipocyte differentiation remains intact, despite expression of the reported adipocyte defying Grem1 in the MSCs and MSC-B7 cells (40). This differentiation potential is highlighted in the pathology associated with skeletal fragility, including increased marrow adiposity due to less physical exertion, aging, and estrogen deficiency (65)(66)(67). The marrow microenvironment and resulting MSCs may react and respond to the increased adiposity, causing an increase in the propensity for MSCs to become adipose or even for existing osteogenic cells to be trans-differentiated into fat.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human data have demonstrated that marrow adipose tissue is context-specific and, in many situations, is inversely related to the structural integrity of the skeleton. 19,[32][33][34] In OP, increased marrow adipocyte production is counterbalanced by decreased generation of osteogenic cells. Many pieces of evidence have indicated an important role for PPARg2 in bone metabolism.…”
Section: Fan Et Almentioning
confidence: 99%